ass1 - P(E^(F or G =P(E^G)or(F^G =P(E^G P(F^G-P(E^F^G =PP...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
P(E^(F or G)) =P((E^G)or(F^G)) =P(E^G)+P(F^G)-P(E^F^G) =PP+PP-P(ø)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 11/17/2011 for the course MUSIC 1001 taught by Professor during the Spring '11 term at Princess Sumaya University for Technology.

Ask a homework question - tutors are online